Continuous and Comprehensive Evaluation a Reform In Evaluations Technique: Enhancing Learning through Continuous and Comprehensive Evaluation (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education aims at making children capable of becomingresponsible, productive and useful members of a society. Knowledge, skills andattitudes are built through learning experiences and opportunities created forlearners in school. It is in the classroom that learners can analyse andevaluate their experiences, learn to doubt, to question, to investigate and tothink independently. The aim of education simultaneously reflects the currentneeds and aspirations of a society as well as its lasting values and humanideals. At any given time and place it can be called the contemporary andcontextual articulations of broad and lasting human aspirations and values. Anunderstanding of learners, educational aims, the nature of knowledge, and thenature of the school as a social organization can help us arrive at principlesto guide classroom practices. Conceptual development is thus a continuousprocess of Deepening and enriching connections and acquiring new layers ofmeaning. Simultaneously theories that children have about the natural andsocial world, develop, including about themselves in relation to others, whichprovide them with explanations for why things are the way they are and therelationship between the cause and its effect. Attitudes, emotions and valuesare thus an integral part of cognitive development, and are linked to thedevelopment of language, mental representations, concepts and reasoning. Aschildren’s metacognitive capabilities develop, they become more aware of theirown beliefs and capable of regulating their own learning.